PENGARUH PENGUASAAN MATA PELAJARAN PRODUKTIF DAN PRAKTIK KERJA INDUSTRI TERHADAP KESIAPAN KERJA SISWA KELAS XI SMK KRISTEN 1 SURAKARTA TAHUN AJARAN 2016/2017 - Wahyu Ariyanti; Baedhowi Baedhowi; Sunarto Sunarto (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
This research aims 1) the effect of productive subject mastery and industrial work practice toward working readiness; 2) the effect of productive subject mastery toward working readiness; 3) the effect of industrial work practice toward working readiness. This research uses descriptive quantitative. The population of research is the student of XI grade of SMK Kristen Surakarta with 125 students. The sample research is 56 students uses proportional random sampling. The technique of collecting data through questionnaire, and documentation. The research also uses multiple linear regression analysis as the technique of analyzing data. The results showed; 1) there is effect of productive subject mastery and industrial work practice toward working readiness of 29,4%; 2) there is effect of productive subject mastery toward working readiness of 13,69%; 3) there is effect of industrial work practice toward working readiness of 16,65%.